Análisis a los estados financieros de la cooperativa de ahorro y crédito obras públicas fiscales de Loja y Zamora del período 2015-2016. - Armijos Hurtado, Cindy Carolina (2018)
The Financial Analysis of the Savings and Credit Cooperative "Fiscal Public Works of Loja and Zamora" for the period 2015-2016, was carried out to fulfill the prerequisite to choose the degree of Engineer in Accounting and Auditing, CPA, and with the purpose of to establish options that help the correct decision making in the entity. The content of the research is based on the general objective where the financial statements of the cooperative were analyzed, in order to contribute to the improvement of the administrative management. The theoretical contents obtained in the classrooms that are related to the financial analysis were supported with the help of a short bibliography, followed by the vertical and horizontal analysis corresponding to the financial statements in 2015 and 2016, the percentage of the accounts was determined. significant that exist within the assets, liabilities, assets, income and expenses, as well as the variations that the items in the study have had from one period to another, establishing the reason, likewise applying indicators with CAMEL and PERLAS methodology , where the financial returns were established that are designed to serve as a guide to the managers and establish a correct decision making, finally the report was made on the results obtained in the course of the analysis, presented strengths, weaknesses and improvement strategies . With the obtained results it was possible to determine that the entity is financially and economically stable, it is recommended to perform Financial Analysis periodically, as well as to apply indicators that will help the correct decision making for the benefit of the Cooperative.